5x=6x+48

Simple and best practice solution for 5x=6x+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x=6x+48 equation:


Simplifying
5x = 6x + 48

Reorder the terms:
5x = 48 + 6x

Solving
5x = 48 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5x + -6x = 48 + 6x + -6x

Combine like terms: 5x + -6x = -1x
-1x = 48 + 6x + -6x

Combine like terms: 6x + -6x = 0
-1x = 48 + 0
-1x = 48

Divide each side by '-1'.
x = -48

Simplifying
x = -48

See similar equations:

| 5x-2+3x-14=0 | | logx=-5.6 | | 2(3x-4)=-22x | | 9 = f3+ 5 | | w^3+7w^2-4w-28=0 | | 3x+5=2(x-5)-x | | f(2)=7x+8 | | 2(x+4)=6x+8 | | 3x+47=122 | | X-0.1X=13 | | -5x+6(x-4)=-16 | | -1/6-(5/8) | | 6(2x-3)-4x+2=4(2x+1)-5 | | -1/8-(5/6) | | 2x^3-27=0 | | 7x-8=x+12 | | 7y-12=6 | | 144=x*4x | | 144=x*2x | | 2n^2-9n+0=0 | | 8c+5=2(4c-8) | | 4y*y=3 | | 5y+10=45 | | -(-m+4m)=-6 | | 2n^2-9n+2=-2 | | 2n^2-9n+2=2 | | x+1=3k-1 | | 2x+1y=3.00 | | 2n^2-9n+2=0 | | 0=3/4x-3 | | 2.88x=9.12 | | 57w=450x |

Equations solver categories